The main role of electronic document exchange technologies in the digitization of the economy in Uzbekistan and their development directions - Toshniyozov, Sherali (GREEN ECONOMY AND DEVELOPMENT, 2024)
The article explores the significance of electronic document exchange technologies in the digitization of Uzbekistan's economy. It highlights the methods used to streamline data exchange processes, enhance efficiency, and ensure security. The study also emphasizes developmental directions, including infrastructure improvement, international integration, and innovative approaches to technological advancement.